ChemInform Abstract: An Efficient Catalytic Method for Regioselective Sulfenylation of Electron‐Rich Aza‐Aromatics at Room Temperature. Issue 21 (2nd May 2013) - Marcantoni, Enrico; Cipolletti, Roberto; Marsili, Laura; Menichetti, Stefano; Properzi, Roberta; Viglianisi, Caterina
Abstract This reaction proceeds with high regioselectivity to yield sulfenyl‐substituted indole and pyrrole derivatives.